Educational technologies of new pedagogical system - Dmitrieva, Nataliia Konstantinovna (Razvitie obrazovaniâ (Online), 2019)
The article is concerned with the problem of information and education system development as a new pedagogical system. The significance of the problem is conditioned by the mounting needs of developing digital economy and inner demand of the individual receiving higher education. The category of «information and education system» was studied and its major characteristic features were revealed; a general definition of the category in focus was formulated. A set of modified pedagogical technologies based on the information and communication technologies’ potential was researched with the purpose to identify its effectiveness on the realization of the «information and education system» as one of the pedagogical conditions. According the author of the article a set of modified pedagogical technologies should include: project based learning technology based on interactive methods of teaching, technology of contextual education, modular technology and proactive teaching technology. The basic principles uniting all chosen technologies are the principle of activity, selfsufficiency, creativity and productivity.